Tax Policy and Business Investment in the United States : Evidence from the 1980's. (IMF Working Papers; Working Paper ;, 1988)
This paper examines the behavior of business fixed investment in the United States in the 1980s. A background discussion of the long-term behavior of the components of business fixed investment is provided, setting the context for the empirical analysis. A standard neoclassical model of business fixed investment is specified and estimated, with output and the cost of capital the primary explanatory variables. Simulation experiments are then conducted with a view to assessing the importance of various contributing factors--in particular tax policy--in influencing the behavior of business fixed investment during the economic expansion that began in late 1982.